META-ANALYSIS OF VARIOUS COLLABORATIVE LEARNING BACKGROUND IN NATURAL SCIENCE TEACHING AND LEARNING PROCESS - Anisa Rizkia; Qurrotul Anfa; Huyteang Meng (INSECTA: Integrative Science Education and Teaching Activity Journal, 2021)
This meta-analysis study aims to determine the background of collaborative learning in science learning. The sample used was purposive sampling related to research on the background of collaborative learning in natural science teaching and learning processwith seventeen research samples. Six classes actions will be used as samples to find the background for the application of collaborative learning in science learning, while the other 11 plus 6 existing classroom action studies were used as supporting materials for the background. Results based on a meta-analysis study, it was found that 29.40% of collaborative learning was motivated by the lack of students' social skills. In addition, there were also 6 problems that underlie related or emerging studies, including the lack of absorption and mastery of student learning, passive students, low student motivation, lack of innovative learning strategies, lack of innovative learning media, lack of social skills of students, low critical thinking skills of students.